An Investigation of Customer’s Emotional Response to Service Failures in Taiwan - Chang, An Ting (2022)
Companies cannot avoid service failure, and the emerging negative emotions after the failed service can directly impact consumers' post-purchase behaviours which may jeopardise the company's profitability. Hence, as consumer sovereignty expands, it is increasingly important to realise how to console dissatisfied customers and eliminate their negative emotions. However, most existing studies were conducted in Western countries, but only a few investigated whether these findings apply to Taiwan. Therefore, this dissertation conducted quantitative research adopting several concepts from earlier field research to explore Taiwanese customers' emotional and behavioural responses after a service failure. The author decided to operate a specific-emotion approach and focus on three distinct negative emotions based on the appraisal theory: anger, regret, and helplessness. Further, this dissertation examines whether different service providers' responses can lessen the customers' negative emotions and desire to harm or avoid the company in Taiwan. The results of this dissertation suggested that the three negative emotions significantly lead to different customers’ post-purchase behaviours, including active coping strategies (spreading negative word-of-mouth and filing complaints) and coping with the problem passively. Additionally, these results uncover that the Taiwanese tend to react differently to what existing studies suggested with a similar failed service scenario and same negative emotions. Furthermore, as the results indicated, service providers’ actions, such as providing information, financial compensation, and communication platforms, would work differently for the three examined negative emotions. Conseqently, it is essential to realise that Taiwanese customers have different reactions and standards for service providers than Western customers when encountering service failure. Accordingly, companies should tailor business decisions to solve service failure to Taiwan’s culture instead of based on unsuitable assumptions.